Newes from the dead : being a true story of Anne Green, hanged for infanticide at Oxford Assizes in 1650, restored to the world and died again 1665 /: being a true story of Anne Green, hanged for infanticide at Oxford Assizes in 1650, restored to the world and died again 1665. (2014) - Hooper, Mary, 1944-
No abstract available